Left atrial appendage occlusion: Percutaneous and surgical approaches in everyday practice - Gofus, Jan; Zacek, Pavel; Shahin, Youssef; Medilek, Karel; Haman, Ludek; Vojacek, Jan (Kardiologia polska, 2024)
Prophylactic left atrial appendage occlusion has been suggested as a means of reducing cardioembolism risk in patients with atrial fibrillation. Its clinical benefits have been discussed together with potential endocrine or hemodynamic adverse effects, with conflicting conclusions. We aimed to provide a thorough overview of the current literature and a recommendation for daily clinical decision-making. A comprehensive Medline search through PubMed was conducted to search for relevant articles, which were further filtered using the title and abstract. Sixty-five articles were selected as relevant to the topic. Concomitant left atrial appendage occlusion during cardiac surgery for other reasons is effective in terms of thromboembolism risk reduction in patients with a history of atrial fibrillation and higher CHA2DS2-VASc scores. Surgical occlusion is safe, and epicardial closure techniques are preferred. Thoracoscopic and transcatheter techniques are also feasible, and the individual treatment choice must be tailored to the patient. The concerns about endocrine imbalance or risk of heart failure after occlusion are not supported by evidence. Current evidence is conflicting with regard to hemodynamic consequences of appendage occlusion.
Keywords: Anticoagulants; cévní mozková příhoda; antikoagulancia; fibrilace síní; lidé; tromboembolie; Thromboembolism; síňové ouško; Atrial Fibrillation; Atrial Appendage; Stroke; Treatment Outcome; výsledek terapie; Humans